Pediatric clinical pharmacology - Seyberth, Hannsjörg W.; Rane, Anders; Schwab, M. (Matthias).; SpringerLink (Online service). (Berlin New York Springer, 2011)
The objective of this volume is to give an overview of the present state of the art of pediatric clinical pharmacology including developmental physiology, pediatric-specific pathology, special tools and methods for development of drugs for children (assessment of efficacy, toxicity, long-term safety etc.) as well as regulatory and ethical knowledge and skills. In the future, structural and educational changes have to lead back to a closer cooperation and interaction of pediatrics with (clinical) pharmacology and pharmacy.
Preface -- Part 1: General Considerations and methodological aspects -- Part 2: Development of pediatric medicines -- Part 3: Specific pediatric pharmacology.
Electronic reproduction.
Keywords: Pediatric pharmacology; Electronic books